On the possibility of an investigation of semiconductor surface properties using ultrasonic surface waves - OPILSKI, Aleksander (Archives of Acoustics, 1976)
The investigations concerning the propagation of surface waves have so far neglected semiconductors. The present paper points out the necessity of taking into account the effect of surface properties on the propagation of surface waves, even for long ultrasonic waves such that A>rD (A —wavelength and rD- Debye radius). Having this in mind some possibilities of determining the electrostatic potential on the basis of acoustical data obtained for the solid material and thin semiconductor layers have been described.